Cancers in Australia in 2010 attributable to overweight and obesity - Bradley J. Kendall; Louise F. Wilson; Catherine M. Olsen; Penelope M. Webb; Rachel E. Neale; Christopher J. Bain; David C. Whiteman (Elsevier, 2015)
Abstract Objectives: To estimate the proportion and number of cancers occurring in Australia in 2010 attributable to overweight/obesity. Methods: We estimated the population attributable fraction (PAF) and number of cancers causally associated with overweight/obesity. We used standard formulae incorporating Australian prevalence data for body mass index (BMI), relative risks associated with BMI and cancer. We also estimated the proportion change in cancer incidence (potential impact fraction [PIF]) that may have occurred assuming that the prevalence of overweight/obesity had remained at 1990 levels. Results: An estimated 3,917 cancer cases (3.4% of all cancers) diagnosed in 2010 were attributable to overweight/obesity, including 1,101 colon cancers, 971 female post‐menopausal breast cancers and 595 endometrial cancers (PAFs of 10%, 8% and 26%, respectively). Highest PAFs were observed for oesophageal adenocarcinoma (31%), endometrial cancer (26%) and kidney cancer (19%). If the prevalence of overweight/obesity in Australia had remained at levels prevailing in 1990, we estimate there would have been 820 fewer cancers diagnosed in 2010 (PIF 2%). Conclusions: Overweight/obesity causes a substantial number of cancers in Australia. Implications: Public health strategies to reduce the prevalence of overweight and obesity will reduce the incidence of cancer, particularly of the colon, breast and endometrium.